Killing me - Gagnon, Michelle (G. P. Putnam's Sons, 2023)
"Amber Jamison cannot believe she's about to become the latest victim of a serial killer-she's savvy and street smart, so when she gets pushed into, of all things, a white windowless van, she's more angry than afraid. Things get even weirder when she's miraculously saved by a mysterious woman...who promptly disappears. Who was she? And why is she hunting serial killers? You'd think escaping one psychopath would be enough, but Amber's problems are just beginning. Her close call has law enforcement circling a past she's tried to outrun. So she flees across the country, ending up at a seedy motel in Las Vegas with a noir-obsessed manager and a sex worker as her unlikely companions...and danger right behind. She's landed in the crosshairs of the world's most prolific killer, caught up in a deadly game that's been going on for years. To survive, she's forced to dust off her old playbook and partner with someone she can't trust. The odds are against her, but sometimes you just have to roll the dice"--